IFS Supplement on Monetary and Financial Statistics. (International Financial Statistics; Vol. 59 , Sept. 2006, 2006)
In this special quarterly supplement to the International Financial Statistics, the IMF is publishing the monetary statistics for those member countries that have commenced the reporting, on a regular basis, of monetary data that accord with the methodology in the IMF's Monetary and Financial Statistics Manual (MFSM), 2000. The format of monetary data reported in the European Central Bank's (ECB) framework, though like the Standardized Report Forms (SRF) format, is designed to accommodate the additional disaggregation required by the ECB. Countries implementing the ECB's monetary data framework include those that belong to European Economic and Monetary Union (Euro Area), several other members of the European Union, and other European countries that have adopted the ECB's framework. Additional countries will be included in future issues of this Supplement, as more countries implement the reporting of SRF-based data. The Supplement will continue to be published until implementation of the SRF-based reporting has been completed by most member countries.